Analisis Unsur Perencanaan dalam Tindak Pidana Pembunuhan Berencana Sebagaimana Pasal 340 KUHP : (Studi Putusan No.709/Pid.B/2019/PN Jmr) - Nyoman Fitriyatun Naziroh; Syarifuddin Syarifuddin; Heriyanto Heriyanto (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The criminal act committed by the perpetrator of premeditated murder is a very heinous act, because the perpetrator has the heart to kill for certain reasons even though he committed an act that is against the law. Criminal liability for the perpetrators of murder, especially premeditated murder, must be enforced. The problem in this study is how to regulate premeditated murder in Indonesia, the factors that cause the crime of premeditated murder and criminal liability for the perpetrators in the crime of premeditated murder. This study uses a normative juridical research method that collects literature data, namely laws and regulations, law books, judges' decisions, mass media and scientific journals related to the problems discussed in this thesis. The results of the research and discussion in this study are regarding the regulation of premeditated murder in Indonesia, which is listed in article 340 of the Criminal Code, the factors that cause premeditated murder are the revenge factor, personal factor, (mental disorder) situational factor, opportunity factor, willingness factor and criminal liability for the perpetrator in the crime of premeditated murder by looking at the elements of the act of resisting or violating law, the willingness of the defendant to be responsible, the element of guilt, the absence of justifying reasons and the reason for forgiveness are punished with the threat of the death penalty or life imprisonment or a maximum penalty of twenty years.